Peningkatan Kesadaran Masyarakat Melalui Edukasi Lingkungan dan Penanaman Pohon Sebagai Strategi Pelestarian Ekosistem das Karang Mumus Kota Samarinda - Muhammad Rizky Alpyan Noor; Muhammad Abdillah Musyaffa; Fenty Fauziah; Muhammad Fitriansyah (Jurnal Ilmu Sosial dan Humaniora, 2026)
The rapid urbanization and industrialization occurring in major cities across Indonesia have exerted significant pressure on environmental quality, particularly on river ecosystems. The Karang Mumus River, a tributary of the Mahakam River, plays a strategic role as a traditional water transportation route, a source of raw water supply, and an urban drainage system. However, the ecological condition of the Karang Mumus River has deteriorated considerably, as indicated by increasing sedimentation, river channel narrowing, and the loss of riparian vegetation. This community service program employed a Participatory Action Research (PAR) approach, a sustainable action-based method that integrates three key elements: participation, action, and environmental impact assessment. The implementation strategy adopted the Service-Learning (SL) method, which combines theoretical foundations of environmental management with direct ecosystem restoration activities in the field. The results of the program demonstrated that the integration of experiential learning through river trekking activities effectively enhanced participants’ ecological literacy. Through direct contextual observations, participants were able to identify various anthropogenic issues along the Karang Mumus River corridor, including the extensive accumulation of domestic waste and river channel constriction caused by informal settlements.